PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, LIKUIDITAS,INVESMENT OPPORTUNITY SET, DAN PERTUMBUHAN LABA TERHADAP KUALITAS LABA PERUSAHAAN (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia periode 2014-2016) - Citra Dewi, 14.05.52.0018; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is toexamines and analyses the effect of firm size, capital structure,liquidity, Invesment opportunity set, and profit growth to earning quality. This research was conducted at manufacturing company listed on Indonesia Stock Exchange (BEI). The sampling method used in this study is purposive sampling with observation period 2014 to 2016 the number of samples obtained as much as 217. The influence between variables is discribed by using multiple regression analysis with SPSS 19 program. The type of data used is secondary data. The results showed that the capital structure and investment opportunity set had a positive and significant effect on earnings quality. Liquidity has a negative and significant effect on earnings quality. While the size of the company, and profit growth does not affect earnings quality. Keywords : company size, capital structure, liquidity, investment opportunity set, profit growth and earnings quality.